2016
DOI: 10.1111/jog.13142
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of disseminated intravascular coagulopathy‐type amniotic fluid embolism: A report of three cases

Abstract: Amniotic fluid embolism (AFE) is a rare complication of pregnancy and its mortality rate is high. There have been few reports of AFE with presence of severe coagulopathy and incoagulable bleeding, and absence of cardiopulmonary symptoms or limited cardiopulmonary symptoms, followed by massive blood loss during delivery. Such cases have been referred to as disseminated intravascular coagulopathy-type AFE, and the characteristics of this condition have been presented previously. Here we report three cases that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Typical symptoms and signs of AFE include rapid deterioration of maternal condition, sudden onset of cardiac arrest or hypotension, dyspnea, and cyanosis. However, consumption coagulopathy without cardiopulmonary arrest was recently proposed as an incomplete form of AFE [15]. Intriguingly, in our study, there were 2 cases (case number 4 and 8) that manifested symptoms of clinical coagulopathy and neurologic signs without cardiorespiratory compromise.…”
Section: Discussionmentioning
confidence: 46%
“…Typical symptoms and signs of AFE include rapid deterioration of maternal condition, sudden onset of cardiac arrest or hypotension, dyspnea, and cyanosis. However, consumption coagulopathy without cardiopulmonary arrest was recently proposed as an incomplete form of AFE [15]. Intriguingly, in our study, there were 2 cases (case number 4 and 8) that manifested symptoms of clinical coagulopathy and neurologic signs without cardiorespiratory compromise.…”
Section: Discussionmentioning
confidence: 46%
“…However, during the cesarean delivery in the present case, fibrinogen level suddenly decreased to 59 mg/dL, which was much lower than that needed to diagnose overt DIC (≤150 mg/dL) . We believe this was because the ruptured dilated veins due to the myometrial sectioning were exposed to amniotic fluid, resulting in a DIC type of amniotic fluid embolism, although there were no severe cardiopulmonary symptoms involved in this case. Previous studies indicated that fibrinogen levels <87 mg/dL were associated with a very high rate (95.2%) of DIC requiring massive transfusions .…”
Section: Discussionmentioning
confidence: 49%
“…There are small numbers of women who present with significant and unexpected hypofibrinogenemia early during the PPH without maternal collapse or other apparent causes of coagulopathy. 61 The etiology of the bleed may be ascribed to other obstetric causes of PPH or obstetric coagulopathy of unknown cause but they may represent part of the AFE spectrum where prompt recognition and treatment is essential. 61…”
Section: Incidence Of Coagulation Abnormalities In Pphmentioning
confidence: 99%
“…61 The etiology of the bleed may be ascribed to other obstetric causes of PPH or obstetric coagulopathy of unknown cause but they may represent part of the AFE spectrum where prompt recognition and treatment is essential. 61…”
Section: Incidence Of Coagulation Abnormalities In Pphmentioning
confidence: 99%
See 1 more Smart Citation